Synopsis of the hymenopteran fauna of Lord Howe Island with a preliminary checklist of species - Jennings, John T.; Austin, Andrew D. (Zootaxa, 2015)
Lord Howe Island is an eroded remnant of a shield volcano approximately 600 km northeast of Sydney, New South Wales, Australia. It has fascinated biologists for more than a century because of its unique and iconic fauna and flora, and was declared a World Heritage Site in 1982. Although the terrestrial invertebrate fauna is reasonably well known for many groups, most Hymenoptera, apart from ants, have received scant attention. Here we use material collected from a recent intensive invertebrate survey, in conjunction with the published literature, to provide an overview of the Hymenoptera known from the island that can act as a basis for future taxonomic and biodiversity research. In doing so, we record 318 species from 31 hymenopteran families from the Island, and assess the proportion that are flightless and likely to be endemic to the island.